How Learning Styles Match Language Learner Educational Technology Study Program in Baturaja University - Yusnilita, Nopa; Afifah, Nurul; Agustina, Aryanti (STKIP PGRI Lubuklinggau, 2024)
Education is a crucial element in equipping students for their future. Each student has a unique way of understanding and absorbing information in every learning session. Engaging English teaching is an art that requires specific styles and techniques, making the learning process more enjoyable, and the study material more easily accepted by students. The researcher applied a qualitative literary research approach, emphasizing the utilization of texts and library literature as the main sources of primary data, involving three stages, namely data reduction, data presentation, and conclusion drawing or verification. Sampling was conducted within Educational Technology Study Program at Baturaja University, and the analysis of the samples was performed using a quantitative method. Learning style refers to the methods and techniques individuals use to learn and process information and knowledge. Students in Educational Technology study program in Baturaja University employ visual, auditory, and kinesthetic learning styles. This is verified by the analysis results, which reveal that 18 (60%) students prefer visual learning, 7 (23.33%) prefer auditory learning, and 5 (16.66%) prefer kinesthetic learning. The research findings demonstrate that studying learning styles has beneficial effects in the learning process, aiding in the development of confidence and autonomy in managing their learning. This, in turn, contributes to an improved overall learning experience.